Amyloid β synaptotoxicity is Wnt‐PCP dependent and blocked by fasudil. Issue 3 (19th October 2017) - Sellers, Katherine J.; Elliott, Christina; Jackson, Joshua; Ghosh, Anshua; Ribe, Elena; Rojo, Ana I.; Jarosz‐Griffiths, Heledd H.; Watson, Iain A.; Xia, Weiming; Semenov, Mikhail; Morin, Peter; Hooper, Nigel M.; et al.
Abstract: Introduction: Synapse loss is the structural correlate of the cognitive decline indicative of dementia. In the brains of Alzheimer's disease sufferers, amyloid β (Aβ) peptides aggregate to form senile plaques but as soluble peptides are toxic to synapses. We previously demonstrated that Aβ induces Dickkopf‐1 (Dkk1), which in turn activates the Wnt–planar cell polarity (Wnt‐PCP) pathway to drive tau pathology and neuronal death. Methods: We compared the effects of Aβ and of Dkk1 on synapse morphology and memory impairment while inhibiting or silencing key elements of the Wnt‐PCP pathway. Results: We demonstrate that Aβ synaptotoxicity is also Dkk1 and Wnt‐PCP dependent, mediated by the arm of Wnt‐PCP regulating actin cytoskeletal dynamics via Daam1, RhoA and ROCK, and can be blocked by the drug fasudil. Discussion: Our data add to the importance of aberrant Wnt signaling in Alzheimer's disease neuropathology and indicate that fasudil could be repurposed as a treatment for the disease. Highlights: Aβ synaptotoxicity is Dickkopf‐1 and Wnt‐PCP dependent. The Wnt‐PCP pathway drives Aβ‐driven synapse loss via RhoA and ROCK. ROCK inhibitor fasudil blocks Aβ‐driven synapse loss and cognitive impairment. Fasudil should be assessed for repurposing for Alzheimer's disease.